Immunotherapy in Cancer: A Combat between Tumors and the Immune System; You Win Some, You Lose Some - Madorsky Rowdo, Florencia Paula; Baron, Antonela; Urrutia, Mariela; Mordoh, José (Frontiers in Immunology, 2015)
Cancer immunotherapy has emerged as a treatment modality, mainly as the result of discoveries in the immune response regulation, including mechanisms that turn off immune responses. Immunogenic cutaneous melanoma is a canonical model for therapeutic immunotherapy studies. "Passive" immunotherapy with monoclonal antibodies (mAbs) has outpaced "active" immunotherapy with antitumor vaccines, and mAbs that antagonize the off responses have been recently introduced in clinical practice. Despite these recent successes, many unresolved practical and theoretical questions remain. Notably unknown are the identity of the lymphocytes that eliminate tumor cells, which white cells enter into tumors, through which endothelium, in what order, and how they perform their task. The parameters of size and location that could be used to determine in which tumors the immune response may be sufficient to eradicate the tumor are yet unknown. Immunotherapy has been so far more efficient to treat solid and hematologic tumors located outside the central nervous system, than primary brain tumors and brain metastases. In contrast to recent advances with mAbs, antitumor vaccine development has been lagging behind. The multiplicity of antigens that must be targeted to achieve significant clinical response is partially responsible for this lag, especially in melanoma, one of the most mutated tumors. Further hampering vaccination results is the fact that tumor elimination by the immune system is the result of a race between tumors with different growth rates and the relatively slow development of the adaptive immune response. The enhancement of the native arm of the immune response or the administration of targeted chemotherapy to slow tumor development, are approaches that should be studied. Finally, criteria used to analyze patient response to immunotherapeutic treatments must be perfected, and the patient populations that could benefit the most from this approach must be better defined.